KENYA Staff Report for the 2001 Article IV Consultation : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2001 Article IV Consultation highlights that Kenya's economic performance during the past decade has been well below its potential. This reflects the failure to sustain prudent macroeconomic policies and the slow pace of structural reform. Consequently, Kenya's real per capita GDP is now lower than it was in 1990, and poverty is much more prevalent. Executive Directors have commended the authorities for achieving a measure of macroeconomic stability during recent years, in difficult circumstances. To help obtain tangible results, they have stressed the importance of departing from the 'stop-go' policies of the 1990s.